Analisis Pencatatan dan Pelaporan Keuangan Berdasarkan Standar Akuntansi Pemerintah Nomor 71 Tahun 2010 Pada Kantor Kecamatan Loa Janan Ilir Samarinda - Ida Rachmawati3, Apriati Uleh1 Elfreda Aplonia Lau2 (EKONOMIA, 2020)
Research objectives are a). Analyzing and evaluating financial records in Loa Janan Ilir Samarinda Subdistrict with the provisions of Government Regulation Number 17 of 2010 concerning Accrual-based Government Accounting Standards (SAP). b). Analyze and evaluate financial reporting or presentation in Loa Janan Ilir Samarinda Subdistrict with the provisions of Government Regulation Number 17 of 2010 concerning Accrual-based Government Accounting Standards (SAP).The theoretical basis used is public sector accounting which focuses on recording and reporting or presenting regional financial reports, Government Regulation Number 71 of 2010 concerning Accrual-based Government Accounting Standards (SAP).The analysis tool used in this study is the comparative method, comparing the financial statements of Loa Janan Ilir Samarinda in 2017 with SAP PP Number 71 of 2010 using the Dean J. Champion formula in 1990. The results showed that 1). The financial records in Loa Janan Ilir Samarinda District in 2017 are in accordance with SAP PP Number 71 of 2010, so the first hypothesis is accepted. 2). Financial reporting or presentation in Loa Janan Ilir Samarinda District in 2017, in accordance with SAP PP Number 71 of 2010, so that the second hypothesis is accepted